A fuzzy logic based model to predict surface hardness of thin film TiN coating on aerospace AL7075-T6 alloy - Zalnezhad, E.; Sarhan, Ahmed Aly Diaa Mohammed; Hamdi, M. (2013)
Aerospace applications and energy-saving strategies in general raised the interest and study in the field of lightweight materials, especially on aluminum alloys. Aluminum alloy itself does not have appropriate wear resistance. Therefore, improvement of surface properties is required in practical applications, especially when aluminum is in contact with other parts. In this work, first titanium nitride (TiN) is coated on aerospace Al7075-T6 in different conditions using PVD magnetron sputtering technique, and the surface hardness of TiN-coated specimens is measured using a micro hardness machine. Second, a fuzzy logic model is offered to predict the surface hardness of TiN coating on AL7075-T6 with respect to changes in input process parameters, direct current (DC) power, DC bias voltage, and nitrogen flow rate. Four membership functions are allocated to be connected with each input of the model. The predicted results achieved via fuzzy logic model are compared to the experimental result. The result demonstrated settlement between the fuzzy model and experimental results with 96.142 accuracy. The hardness of titanium nitride-coated specimens is increased significantly up to 720 HV, while the hardness of uncoated specimens was 170 HV.